Implementation Enterprise Resource Planning (ERP) ODOO Version 15.0 Manufacturing Module at CV. Razzaq Berkah Mulia - Setiawan, Ibnu Fajar; Siswanto, Teddy; Sugiarto, Dedy (Penerbitan Universitas Trisakti, 2024)
In the modern era, digitalization has had a significant impact on various business fields, with technology being the main key in fascilitating company performance. Digitalization of company systems is now an obligation, data integration is essential for analysis that supports company progress. ERP is software that simplifies company operations by integrating various business application modules such as Inventory, Accounting, Sales, Point of Sales, Manufacturing, Contact, Website, and Purchasing. CV Razzaq Berkah Mulia, which has the potential to compete with international furniture companies, has not fully adopted information systems in its management. This lack of digitalization can lead to losses and recording errors that hinder their business performance. An optimized and valid implementation of Odoo ERP is essential to improve the quality and operational efficiency of CV Razzaq Berkah Mulia. This Implementation will go through several phases, namely Discovery and Planning, Design, Development, Testing, Deployment, and Support. At the Discovery and Planning stage, the company needs will be identified and an implementation strategy will be planned. The Design stage will design the system as per requirements, while the Development Stage will involve the creation and configuration of the system. At the testing stage, the system willl be tested to ensure its functionality, and the Deployment stage will involve launching the system into the operational environtment. Finally, the Support stage will provide post-implementation support. The final result of this development can be accepted and implemented for the implementation of Odoo at CV. Razzaq Berkah Mulia through UTAUT with a satisfaction value of Performance Expectancy 88%, Effort Expectancy 88%, Supporting Facilities 88,4%, Facilitating Conditions 91%, Attitude Towards Technology 89,2%, Behavioral Intention 90,8%.